Academic Reading, Writing, and Publishing in Nepal: Initiation from Institute of Medicine - Singh , Yogendra P (Journal of Institute of Medicine Nepal, 2021)
Institute of Medicine (IOM) under Tribhuvan University, the first medical school in Nepal, was established in 1972 to produce different categories of health professionals needed for the country. Being the premier academic institute, academic reading, writing, and publishing were the initiatives taken by the institute in Nepal. These academic activities have been improvised with each academic department of the institute. IOM has a motto of academic excellence can be achieved by academic reading, writing, and publishing.